Analysing halal smes' behaviour intention in adopting IR4.0 on the east coast of peninsular malaysia - Salme, Yahya (2024)
In order to guarantee and fulfil market needs for high-quality Halal food products, the Government of Malaysia has encouraged Small and medium enterprises (SMEs) to explore IR4.0 technologies by providing training and funds. Nevertheless, fewer SMEs are taking this opportunity to increase and upgrade the technology used in business operations. Thus, this research serves as an initial step in understanding and filling the research gaps primarily by offering insights to establish the strategic view of SMEs' middle manager to top manager behaviour intention in using IR4.0 technology. Besides that, this quantitative research uses surveys as a research method and uses the Unified Theory of Acceptance and Use of Technology (UTAUT) and Institutional Theory as theoretical background. Next, to fill the study gap, the researchers varied the study by testing the effect of voluntariness of use as a moderator on the independent and dependent variables. The researcher also tested new factors of Muamalat E-Commerce in UTAUT theory. The target samples for this research is 218 middle to top manager in SMEs Companies in East Coast Malaysia (Pahang, Terengganu, and Kelantan) that produce Halal product for food/drink/supplement food. As for data analysis, partial least squares structural equation modelling (PLS-SEM) is employed. The results suggest a good fit to the data, with good convergent and reliability stability and discriminant validity. The SmartPLS and Statistical Program for Social Science (SPSS) software were used in this study. The result of the study is that there is a positive relationship in the acceptance of IR 4.0 technology towards Halal SMEs for the food industry in Malaysia. At the same time, institutional motivation did not give a significant result. Although institutional motivation does not have a positive relationship with SMEs' behaviour intention, the findings show that voluntariness of use as a moderator significantly affects both theories used in this study. The findings have implications for knowledge of theories and practices and contribute to the IR4.0 technology in the halal food industry. Furthermore, the study contributes to the growing halal technology literature and recommends potential research directions.